UPAYA MENGIDENTIFIKASI RISIKO DALAM MENGHINDARI ANCAMAN BAHAYA DI PAUD MELATI 02 - Hanif, Rizki; Hidayat, Wahyu (Program Studi Manajemen Pendidikan Islam, 2023)
This research discusses efforts to identify risks to avoid potential hazards at the Melati 02 Early Childhood Education Centre (PAUD) which is located in Bojong Pulus Village Rt. 04 Rw. 02, Banjaran Wetan, Banjaran District, Bandung Regency, West Java Province.. The background of the study emphasizes the need for a deeper understanding of risk identification and the role of the physical environment and security policies in the PAUD setting. The research aims to determine the risk identification process, potential hazards around the PAUD Melati 02, and ways to minimize and prevent these risks. The study also highlights the benefits of risk management in enhancing operational efficiency, protecting shareholder value, and minimizing losses. The research methodology involves a qualitative approach with data collection techniques such as observation, interviews, and documentation. The findings reveal identified risks at the PAUD Melati 02, including accident and environmental risks, and emphasize the importance of risk mitigation to minimize negative impacts. The study concludes by acknowledging its limitations and inviting constructive criticism and suggestions for future improvements. Overall, the research provides practical guidance for PAUD management and relevant stakeholders in enhancing risk identification and ensuring the safety of children in the environment.